2020
DOI: 10.3390/mi11050512
|View full text |Cite
|
Sign up to set email alerts
|

Micromachining of High Quality PMN–31%PT Single Crystals for High-Frequency (>20 MHz) Ultrasonic Array Transducer Applications

Abstract: A decrease of piezoelectric properties in the fabrication of ultra-small Pb(Mg1/3Nb2/3)–x%PbTiO3 (PMN–x%PT) for high-frequency (>20 MHz) ultrasonic array transducers remains an urgent problem. Here, PMN–31%PT with micron-sized kerfs and high piezoelectric performance was micromachined using a 355 nm laser. We studied the kerf profile as a function of laser parameters, revealing that micron-sized kerfs with designated profiles and fewer micro-cracks can be obtained by optimizing the laser parameters. The dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…We have found similar patterns in several experiments, and our previous studies have shown similar results [ 28 , 29 ]. In addition, some related research reports are also consistent with our results [ 32 , 33 , 34 , 35 ].…”
Section: Resultssupporting
confidence: 93%
“…We have found similar patterns in several experiments, and our previous studies have shown similar results [ 28 , 29 ]. In addition, some related research reports are also consistent with our results [ 32 , 33 , 34 , 35 ].…”
Section: Resultssupporting
confidence: 93%
“…A variety of piezoelectric materials, including piezoelectric ceramics [13,14], ferroelectric polymers [15], and ferroelectrets [16], have been adopted in energy harvesting. Among them, the ferroelectret is a relatively new one that was first used in energy harvesters in 2012 [17].…”
Section: Introductionmentioning
confidence: 99%